Optimization of warm mix asphalts using different blends of binders and paraffin wax contents - Silva, Hugo Manuel Ribeiro Dias da (2010)
In road construction, several processes and products are now available to produce environmentally friendlier warm mix asphalts, including the use of synthetic paraffin wax additives. These additives facilitate the production of energy efficient asphalt mixtures at reduced manufacturing and construction temperatures. However, their sustainability during the road life cycle can only be obtained by optimizing the mixture's performance. Thus, the objective of this work was to assess the properties of different blends of base bitumens (softer to harder ones) containing a range of synthetic wax contents, as well as the performance of the corresponding warm mix asphalts, that could ultimately lead to more sustainable mixtures. It was concluded that different blends should be selected to maximize the temperature reduction, the fatigue or the rut resistance, without compromising the other properties of the mixture. (C) 2010 Elsevier Ltd. All rights reserved.